PENGOLAHAN SAMPAH RUMAH TANGGA MENJADI PRODUK BERNILAI PADA NASABAH BANK SAMPAH LIDAH MERTUA - Rini Rahmahdian; Amra Ausri; Musbatiq Srivani; Wahyuni Eloisa Marinda; Lukman Lukman (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Lidah Mertua Waste Bank has been a garbage bank built by the team since last year. This activity aims to increase household waste's added value by processing it into recycled goods that have higher economic value. The methods used include extension methods, lectures and interactive discussions, training, and processing household waste into recycled economic value items and the essential provision of cost analysis. The object of activity is housewives who are customers of the Tongue-In-Law Waste Bank, Bungo Pasang Village, Tabing Padang. The community service activity was attended by 45 participants consisting of 5 waste bank managers and 40 waste bank customers, Lidah Mertua. The results of the activities obtained have been able to increase the number of customers and improve service to customers due to using some operational assistance from the previous year's service activities. This activity can also improve partners' and customers' skills in processing household waste before selling it to collectors. It is hoped that this activity can strengthen customer households' economic resilience and increase the role of women in supporting the family economy through household waste management.